Study on the heat transfer of the plate-fin heat sink under impinging jet cooling. (29th June 2011) - Lin, David T.W.; Li, Hung-Yi; Hu, Yuh-Chung
This paper aims at investigating the heat transfer phenomena of the plate-fin heat sinks under impinging jet cooling. The impinging jet cooling has the advantage of larger heat removal. The finite element method is used to simulate the heat transfer phenomena of the plate-fin heat sinks under impinging jet cooling. The simulation results are verified by comparing with the experimental data. The parameters discussed in this study include the fin size, the Reynolds number and the impingement distance. The results of this study show that the effect of Reynolds number dominates to the heat removal. The heat removal increases with the Reynolds number obviously. In addition, the temperature profile on the fin surface is affected by the arrangement of the fin.